Victims as security threats refugee impact on host state security in Africa - Mogire, Edward O. (Global security in a changing world, 2009)
The refugee phenomenon is a major force in international politics, particularly in sub-Saharan Africa, where refugees are major actors in the affairs of their home and host countries. This book analyses why refugees, victims of insecurity due to conflict or persecution, have themselves become viewed by scholars and practitioners as a security threat. Using Kenya and Tanzania as case studies, the work also examines responses made to this threat